Unveiling the dynamics of team cognition in emergency response teams - Esmaeili, Reza; Yazdi, Mohammad; Rismanchian, Masoud; Shakerian, Mahnaz (Frontiers in Psychology, 2025)
BackgroundEffective emergency response in various industries depends on the synergy between team coordination and cognitive abilities. Industries should prioritize investing in the development of team cognition to improve readiness and ensure swift, effective responses to emergencies and crises. This study aimed to identify and model factors influencing team cognition within Emergency Response Teams (ERTs).MethodsThis cross-sectional study undertook two principal phases: qualitative research using meta-synthesis and quantitative research using Best Worst Method (BWM), Interpretive Structural Modeling (ISM), and Fuzzy Cognitive Mapping (FCM). These methods were employed to assign weights to factors, establish their hierarchy, and determine cause-and-effect relationships among team cognition shaping factors (TCSFs).ResultsThrough a comprehensive evaluation of the articles, 13 dimensions were identified as the primary TCSFs influencing team cognition. The reliability of the extracted factors was validated using the Kappa indicator, with a value of 0.63 signifying an acceptable level of agreement. Using BWM analysis, “Team maturity (The team members’ harmonization)” and “Inefficient 4Cs (communication, coordination, cooperation, and collaboration)” were identified as the most influential factors shaping team cognition, with weights of 0.132 and 0.112, respectively. ISM analysis revealed “Improper team training programs” as a critical independent factor influencing other dimensions. FCM modeling further emphasized the significance of “Failure in decision-making” and “Leadership behavior and performance” as pivotal contributors to team cognition, with “Team maturity” and “Inefficient 4Cs” achieving the highest centrality scores of 13.44 and 13.28, respectively.ConclusionStakeholders can enhance team performance and effectiveness in emergency situations by understanding the relative importance of various factors, their hierarchical relationships, and the causal links between them. This allows for informed decision-making and targeted interventions, such as training programs to improve team maturity and team communication.